If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -67 = 3 + 7x Solving -67 = 3 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. -67 + -7x = 3 + 7x + -7x Combine like terms: 7x + -7x = 0 -67 + -7x = 3 + 0 -67 + -7x = 3 Add '67' to each side of the equation. -67 + 67 + -7x = 3 + 67 Combine like terms: -67 + 67 = 0 0 + -7x = 3 + 67 -7x = 3 + 67 Combine like terms: 3 + 67 = 70 -7x = 70 Divide each side by '-7'. x = -10 Simplifying x = -10
| -10x-22=-212 | | 24x-4x+72x+100=0 | | 3(4x+3)+6x+1=43 | | 4x+36x=93 | | 3+21=15 | | 3+21=21 | | 0.625(a-2)= | | m+3(m-4)=20 | | 4(5-x)=-(1+x) | | 2+4(x+6)=4(2x+3)+6 | | 7(4+n)=4n+37 | | 2(m+5)=16 | | 54+2x=180 | | 4(2x+3)=11x+6 | | 20=5y+5 | | 180=2x-18 | | 525.00+0.21x=600 | | 2t+7=t+9 | | 76-x=3x | | 7n+2=5n+20 | | 9x+4=8x+7 | | 4t^2+48t=160 | | -2v^2-1v+12=-3v^2+6v | | 2x+4y+.25z=100 | | (-8/5)x-6=-54 | | 4m+4=4(m+1) | | 6x-4+4x-6=180 | | 2x+46+x-18+x=180 | | y^2+2xy-3x^2=0 | | 525.00+0.21x=850.00+0.31x | | 2x+46+x-18=180 | | 525.00+0.21x=850.00+0.31 |